Components of party polarization in the US House of Representatives. (October 2016) - Brunell, Thomas L; Grofman, Bernard; Merrill, Samuel
We specify the level of polarization in a two-party legislature as an explicit function of three factors: (1) the ideological heterogeneity of district median voters, (2) the distance between candidates of different parties in the same or ideologically comparable districts, and (3) partisan bias in choosing between candidates equidistant from the median voter. Our key empirical finding, reinforced by two alternative methods of calculation, is that, while changes in each factor have contributed to the present day extremely high level polarization in the US House of Representatives, at least 80% of the growth in that polarization from 1956 through 2008 can be attributed to a dramatic increase in the second of these factors: party differentiation at the district level.